Effect of Free Radicals and Antioxidants on Postmenopausal Osteoporosis - Yalin, Serap; Bagis, Selda; Cenk Aksit, S.; Arslan, Hakan; Erdogan, Canan (Asian Journal of Chemistry, 2010)
In the present work, the effect of free radicals and antioxidant enzymes on postmenopausal osteoporosis and the relationship between free radicals, bone mineral density and estrogen levels in postmenopausal women has been investigated. The study population consisted of 30 osteoporotic female patients and 30 control subjects. Venous blood samples of patients and controls were collected and analyzed for femoral and lumbar bone mineral densities (BMD), nitric oxide (NO), malondialdehyde (MDA) and estrogen levels and glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities. In the osteoporotic group, increased NO and MDA levels and decreased GPx activities and BMD values were observed. No significant differences in estrogen levels and SOD activities were obtained between control and osteoporotic group. Although significant negative correlations between the lumbar BMD and MDA (r = –0.300; p = 0.040) and lumbar BMD and NO (r = –0.303; p = 0.038) levels were observed, a significant positive correlation between the lumbar BMD and GPx (r = 0.382; p = 0.008) was observed. There was no correlation between the estrogen levels, BMD, free radicals and antioxidants. Based on our findings it may be suggested that the balance between oxidant and antioxidant defense mechanisms is impaired in postmenopausal osteoporosis and the negative correlation between BMD and NO and MDA values might demonstrate that free radicals cause increase of osteoclastic activity.